Crescimento de recém-nascidos pré-termo durante internação neonatal e sua relação com as habilidades orais - Vargas, Camila Lehnhart (2014)
Growth in the neonatal period is a major concern for the infant development, considering the association with problems in a short or long term period, especially related to the neurodevelopment. The purpose of this study was to assess the preterm newborns growth during the neonatal hospitalization and its relation to oral feeding skills. Fifty one preterm newborns hospitalized in the Neonatal Intensive Care Unit at The University Hospital of Santa Maria, from July of 2012 to March of 2013, were included in this study. The assessment of oral feeding skills, according to Lau and Smith (2011), was performed following the medical prescription for the first oral feeding (OF). The variables: weight, length and head circumference were measured at birth, at release of oral feeding, at full oral feeding and at hospital discharge. The Fenton s curves (2003) were utilized as reference to evaluate the growth. The results show that at birth, 71% of the preterm newborns were adequate for gestational age, most of them being male (53%) and had 33,6 (±1,5) weeks of gestational age. The average length of hospital stay was 31 (±15,6) days. On average, the weight increased 648 g/months, the length 4,8 centimeters/months and the head circumference 3,2 centimeters/months. Twenty five percent of the preterm newborns were below the percentile 10° for the weight at birth, with increase in this percentage to 57% at hospital discharge. However, the length (33% to 31%) and the head circumference (20% to 15%) remained preserved. The averages of anthropometric variables were not related to the level of oral feeding skills. However, the transition time from the tube to full oral feeding (p=0.0116) and the length of hospitalization was lower in infants with the highest level of oral feeding skills. In conclusion, there was growth of preterm newborns during the hospitalization, being adequate considering the length and head circumference. The oral feeding skills level did not influence the anthropometric variables, however, positively affected the transition time from the tube to full oral feeding and the length of hospitalization.